Efficacy of Repetitive Transcranial Magnetic Stimulation Combined With Visual Scanning Treatment on Cognitive-Behavioral Symptoms of Unilateral Spatial Neglect in Patients With Traumatic Brain Injury: Study Protocol for a Randomized Controlled Trial - Di Gregorio, Francesco; La Porta, Fabio; Lullini, Giada; Casanova, Emanuela; Petrone, Valeria; Simoncini, Loredana; Ferrucci, Enrico; Piperno, Roberto (Frontiers in Neurology, 2021)
Left hemispatial neglect (LHSN) is a frequent and disabling condition affecting patients who suffered from traumatic brain injury (TBI). LHSN is a neuropsychological syndrome characterized clinically by difficulties in attending, responding, and consciously representing the right side of space. Despite its frequency, scientific evidence on effective treatments for this condition in TBI patients is still low. According to existing literature, we hypothesize that in TBI, LHSN is caused by an imbalance in inter-hemispheric activity due to hyperactivity of the left hemisphere as observed in LHSN after right strokes. Thus, by inhibiting this left hyperactivity, repetitive Transcranial Magnetic Stimulation (rTMS) would have a rebalancing effect, reducing LHSN symptoms in TBI patients. We plan to test this hypothesis within a single-blind, randomized SHAM controlled trial in which TBI patients will receive inhibitory i-rTMS followed by cognitive treatment for 15 days. Neurophysiological and clinical measures will be collected before, afterward, and in the follow-up. This study will give the first empirical evidence about the efficacy of a novel approach to treating LHSN in TBI patients.